Adsorptive removal of methylene blue by commercial coconut shell activated carbon / Ramlah Abd Rashid, Mohd Azlan Mohd Ishak and Kasim Mohammed Hello. - Abd Rashid, Ramlah; Mohd Ishak, Mohd Azlan; Mohammed Hello, Kasim (2018)
This paper shows the using of commercial coconut shell activated carbon (CCS-AC) as an alternative adsorbent for the removal of methylene blue (MB) from aqueous solution. The physicochemical properties of the CCSAC were undertaken using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and pH Point of Zero Charge (pHpzc) method. Batch adsorption experiments were conducted to study the influence of adsorbent dosage (0.02 – 0.50 g), pH (3 – 10), MB concentration (25 – 400 mgL-1) and contact time (0 – 36 hours) on the adsorption of the MB. The kinetic adsorption was well described by the Pseudo Second Order model and the Langmuir model described the adsorption behavior at equilibrium. The maximum adsorption capacity (qmax) of CCS-AC obtained was 149.25 mg/g at 303 K.